Driving the Future: An Analysis of Total Cost of Ownership for Electrified Vehicles in North America - Patrycja Soszynska; Huda Saleh; Hana Kar; Lakshmi Varaha Iyer; Caniggia Viana; Narayan C. Kar (World Electric Vehicle Journal)
As the number of electric vehicles (EVs) on North American roads continues to rise, driven by the shift toward sustainable transportation, understanding the economic implications of this transition is crucial. This review paper prioritizes an evaluation of the Total Cost of Ownership (TCO) for various types of EVs, providing insights into how different driving profiles align with the financial benefits of EV adoption. It demonstrates that at-home charging and government incentives are pivotal in reducing TCO. The analysis also offers a comprehensive overview of the factors driving EV growth, including declining operating and maintenance costs. Additionally, the paper explores adoption rates, charging infrastructure, and other non-monetary factors that influence consumer decisions in the shift to EVs. Conclusions emphasize that while EVs offer a financial advantage for many drivers, the success of broader adoption depends on decreasing the initial cost of EVs, developing charging infrastructure, and investing in charging networks.